Strategi jitu pemasaran lumpia kriuk: Camilan favorit di era digital - Widyastuti, Annisa (Maliki Interdisciplinary Journal, 2025)
Lumpia Kriuk is a snack food packaged in a modern way to attract consumers in the digital age. Increasingly fierce market competition has forced businesses to devise efficient marketing strategies in line with technological advances. This article aims to outline a brilliant marketing strategy for Lumpia Kriuk, so that it can become a favorite snack among the public, especially the younger generation. The approach used in this study employs a descriptive qualitative research method, focusing on a case study of SMEs marketing Lumpia Kriuk online. The key strategies include leveraging social media platforms such as Instagram and TikTok, digital branding, collaborating with influencers, and promoting through delivery services. The findings indicate that the use of visually appealing content and active engagement with consumers significantly contribute to enhancing product visibility and sales. This digital strategy also enables expansion into broader markets at more efficient costs. In short, a consistent digital marketing strategy can position Lumpia Kriuk as a popular snack among consumers in the modern era.